Crystallization and destabilization of eudialyte-group minerals in peralkaline granite and pegmatite: a case study from the Ambohimirahavavy complex, Madagascar. (28th February 2018) - Estrade, Guillaume; Salvi, Stefano; Béziat, Didier
Abstract: Eudialyte-group minerals (EGM) are very common in highly evolved SiO2 -undersaturated syenites and are characteristic minerals of agpaitic rocks. Conversely, they are extremely rare in peralkaline granites, with only a handful of EGM occurrences reported worldwide. Here, we study two new examples of EGM occurrence in two types of peralkaline pegmatitic granites from the Cenozoic Ambohimirahavavy complex, and assess the magmatic conditions required to crystallize EGM in peralkaline SiO2 -oversaturated rocks. In the transitional granite (contains EGM as accessory minerals) EGM occur as late phases and are the only agpaitic and major rare-earth element ( REE ) bearing minerals. In the agpaitic granite (contains EGM as rock-forming minerals) EGM are early-magmatic phases occurring together with two other agpaitic minerals, nacareniobsite-(Ce) and turkestanite. In these granites, EGM are partly-to-completely altered and replaced by secondary assemblages consisting of zircon and quartz in the transitional granite and an unidentified Ca-Na zirconosilicate in the agpaitic granite. Ambohimirahavavy EGM, as well as those from other peralkaline granites and pegmatites, are richer in REE and poorer in Ca than EGM in nepheline syenites. We infer that magmatic EGM are rare in SiO2 -oversaturated rocks because of low Cl concentrations in these melts. At Ambohimirahavavy, contamination of the parental magma of the agpaitic granite with Ca-rich material increased the solubility of Cl in the melt promoting EGM crystallization. In both granite types, EGM were destabilized by the late exsolution of a fluid and by interaction with an external Ca-bearing fluid.